Effects of injectable aminoglycosides on the auditory performance of individuals with drug resistant tuberculosis in Osun State, Nigeria (2018)
Ototoxicity caused by injectable aminoglycosides are capable of causing cochleotoxicity which is characterised as death of auditory hair cells (hearing loss) and vestibuiotoxicity manifesting as balance disorders. Ototoxicity is always as a result of insidious effects of aminoglycosides on auditory system, with a kind of irreversible (permanent) hearing loss which is common among individuals being treated for Drug Resistant Tuberculosis (DRTB). Therefore, this study examined the effect of injectable aminoglycosides on the auditory performance of patients with DRTB in Osun state. Twenty (20) DRTB patients comprising of 14 males and 6 females were purposively selected to participate in this ex post facto research. Instruments used include Otoscope to diagnose infection of the middle ear and outer parts of the ear, Maico ST 20 portable diagnostic audiometer to determine the hearing threshold of the participants, and audiograms to record the test results. Baseline audiometry revealed that 35% of the participants had mild hearing loss before commencement of treatment with injectable aminoglycosides, while 70% of the participants had severe to profound hearing loss after completion of injectable aminoglycosides. 65% of the participants had tinnitus in addition to hearing loss, while 55% had high frequency loss only. Therefore, health workers should ensure that people with DRTB are well educated about the side effects of injectable aminoglycosides and be encouraged to access audiologic follow up and rehabilitation, while alternative injectable drugs with reduced or milder side effects are employed for treatment of Drug Resistant Tuberculosis.